2018
DOI: 10.1007/s10802-018-0461-3
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Trauma Symptoms in the Association between Past and Future Teen Dating Violence Victimization

Abstract: We examined whether the frequency of recent physical and sexual teen dating violence (TDV) victimization is positively associated with trauma symptom clusters (re-experiencing, avoidance, and hyperarousal), and whether these symptom clusters, in turn, are positively associated with the frequency of later TDV victimization. Participants were recruited primarily from truancy courts, and the sample consisted of 108 (47% female) 14-to-17-year-olds. Participants completed three assessments, spaced three months apar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…However, not all relevant information regarding risk factors for repeat victimization may be contained within official police records. In line with previous research, this study showed that words related to substance use, psychological distress, and family connections were associated with an increased risk of repeat victimization use (Gong, Kamboj, et al, 2019; Lawyer et al, 2006; López-Martínez et al, 2018; Rancher et al, 2019). To develop more knowledge on the risk factors of repeat victimization, future studies could focus on unstructured police information to identify other risk factors and explore whether information on these risk factors could, for example, be collected through an additional questionnaire.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, not all relevant information regarding risk factors for repeat victimization may be contained within official police records. In line with previous research, this study showed that words related to substance use, psychological distress, and family connections were associated with an increased risk of repeat victimization use (Gong, Kamboj, et al, 2019; Lawyer et al, 2006; López-Martínez et al, 2018; Rancher et al, 2019). To develop more knowledge on the risk factors of repeat victimization, future studies could focus on unstructured police information to identify other risk factors and explore whether information on these risk factors could, for example, be collected through an additional questionnaire.…”
Section: Discussionsupporting
confidence: 91%
“…Repeat victimization has theoretically been explained by individual risk factors such as biological aspects (e.g., gender, physical vulnerability), risky lifestyles, (e.g., staying out late drinking), and occupation (e.g., working nightshifts) (Nagin & Paternoster, 2000). Furthermore, previous victimization experiences may lead to psychological distress, risky lifestyles, and substance use, which may increase the risk of repeat victimization (Gong, Kamboj, et al, 2019;López-Martínez et al, 2018;Rancher et al, 2019). Previous studies employing a text mining approach to police data identified individuals or incidents of interest by using custom-made dictionaries containing words related to these risk factors (Elzinga et al, 2010;Haleem et al, 2019;Karystianis et al, 2018Karystianis et al, , 2019Karystianis et al, , 2020Poelmans et al, 2010).…”
Section: Risk Assessment In the Police Contextmentioning
confidence: 99%
“…First, the data are nonexperimental, precluding conclusions about causal relations. For example, it is possible that mental health symptoms render youth more vulnerable to experiencing and reporting violence exposure (Jouriles et al, 2017;Rancher et al, 2019). Second, the sample was smaller than ideal for a study of this nature, which limited our ability to conduct meaningful analyses to test for differences across ethnoracial groups.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, recent studies tend to focus extensively on teen dating violence, with equivocal results on the ratio of male and female victimization (Cascardi & Jouriles, 2018; Liu et al, 2018; Rancher et al, 2019; Ruel et al, 2020). However, the increasing number and severe consequences of female college students’ victimization in intimate relationships (Han & Lim, 2019) still highlight the need to specify the age group and concentrate on the gendered experiences of violence recipients.…”
Section: Literature Reviewmentioning
confidence: 99%